Leveraging female partner influence in health interventions: a study on prostate cancer screening uptake among men in rural Kiambu County, Kenya - Kimani, Peterson K.; Muchiri, Joseph; Nyongesa, Margaret W. (International Journal Of Community Medicine And Public Health, 2024)
Background: Globally, prostate cancer is the second most common cancer affecting men, with considerably high fatality rates. The aim of this study was to assess the effect of a female partner-led brochure method on perception, attitude, and cultural beliefs toward the intention of prostate cancer screening among men in rural Kiambu County, Kenya. Methods: The research adopted a randomized controlled trial design. Multistage sampling was employed in this study. The Chi-square test was used to assess differences in perception, attitude, and cultural beliefs towards intention to undergo prostate cancer screening (PCS) between the control and intervention groups at baseline and end line. Further, data were subjected to structural equation modeling to assess the influence of perception, attitude, and cultural beliefs on PCS intention pre-and post-intervention. Results: The results revealed no significant difference in perception between the control and intervention groups at baseline and end-line. Regarding attitude, there was a 39.8% and 24.7% increase in positive attitudes in the group that used gain-framed and loss-framed brochure methods, respectively, at the end line. In the end, there was a significant reduction in the number of respondents who had fatalistic beliefs, whereby 23.1% and 13.2% of the respondents in the groups’ intervention used gain-framed and loss-framed brochures, respectively. Conclusions: The study recommends the implementation of female partner-led interventions using gain-framed messaging in prostate cancer screening campaigns, as this approach demonstrated superior effectiveness in improving attitudes, reducing fatalism beliefs, and increasing the perceived benefits of screening among men.